2007
DOI: 10.1016/j.cellbi.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin supraorganization, DNA fragmentation, and cell death in erythrocytes of the rattlesnake, Crotalus durissus terrificus (Serpentes, Viperidae), infected with the protozoan, Hepatozoon spp. (Apicomplexa, Hepatozoidae)

Abstract: Forms of the protozoan of the Hepatozoon genus are detected free in the circulation and also within some of the erythrocytes of infected snakes. In healthy snakes, DNA fragmentation and cell death usually affect a few circulating erythrocytes in agreement with the long life span expected for these cells. In the present study we investigated whether infection by Hepatozoon spp. affected the incidence of DNA fragmentation and cell death in erythrocytes from the rattlesnake, Crotalus durissus terrificus. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…c c e p t e d M a n u s c r i p t protozoan (Hepatozoon spp.) a higher level of damage in the erythrocyte DNA was found compared to the erythrocyte DNA from non-infected snakes[277].…”
mentioning
confidence: 77%
“…c c e p t e d M a n u s c r i p t protozoan (Hepatozoon spp.) a higher level of damage in the erythrocyte DNA was found compared to the erythrocyte DNA from non-infected snakes[277].…”
mentioning
confidence: 77%
“…The finding of Feulgen-DNA values after the acid hydrolysis for 50 and 90 min generally much closer in M. quadrifasciata than in M. rufiventris indicated that DNA depurination occurs faster in M. quadrifasciata (Sandritter et al, 1965;Mello, 1979Mello, , 1983Miyamoto et al, 2005;Miyamoto and Mello, 2007). The faster depurination response in M. quadrifasciata may be promoted by its less packed chromatin states in comparison to M. rufiventris.…”
Section: Discussionmentioning
confidence: 98%
“…Acid hydrolysis was done in 4 M HCl at 25 C for 50 or 90 min followed by treatment with Schiff reagent for 40 min. Mild acid hydrolysis conditions as those used here are considered to be more suitable for the discrimination of differences in Feulgen hydrolysis kinetics provided by differential DNA depurination (ascending branch of the hydrolysis curve) or apurinic acid solubilization (descending branch of the hydrolysis curve) (Sandritter et al, 1965;Mello, 1979Mello, , 1997Mello and Vidal, 1980;Miyamoto et al, 2005;Miyamoto and Mello, 2007). The hydrolysis times were chosen after a preliminary test which revealed that at the time of 90 min a maximal depurination occurred for the DNA of both species.…”
Section: Feulgen Stainingmentioning
confidence: 99%
See 1 more Smart Citation